1999
DOI: 10.1017/s0016672398003486
|View full text |Cite
|
Sign up to set email alerts
|

The full-sib intercross line (FSIL): a QTL mapping design for outcrossing species

Abstract: A full-sib intercross line (FSIL) is constructed in an outcrossing species by mating two parents and intercrossing their progeny to form a large intercross line. For given statistical power, a FSIL design requires only slightly more individuals than an F2 design derived from inbred line cross, but 6-to 10-fold fewer than a half-sib or full-sib design. Due to population-wide linkage disequilibrium, a FSIL is amenable to analysis by selective DNA pooling. In addition, a FSIL is maintained by continued intercross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
12
0
2
Order By: Relevance
“…2002). In chickens, two experimental designs, the advanced intercross line (Darvasi & Soller 1995) and the full sib intercross line (FSIL) (Song et al. 1999), are suitable for detection as well as fine‐mapping of QTL.…”
Section: Introductionmentioning
confidence: 99%
“…2002). In chickens, two experimental designs, the advanced intercross line (Darvasi & Soller 1995) and the full sib intercross line (FSIL) (Song et al. 1999), are suitable for detection as well as fine‐mapping of QTL.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming codominance at the QTL, the contrast values will be δ D =d for the BC design and δ D =2d for the F 2 and AIL designs. The effect for the FSIL designs approaches δ D =2d, depending on the specific configuration of the marker and the QTL alleles (Song et al 1999). The contrast value for the RIL design depends on the number of individuals phenotyped in each line, and will be δ D =2d/σ f , where σ f 2 is the variance among means of inbred lines.…”
Section: Resultsmentioning
confidence: 99%
“…In the F 2 and AIL designs one quarter of the population are in each of the two contrasted marker genotype groups, so that k D =0.25. In the FSIL population, at the optimal configuration of marker and QTL alleles, the proportions will be the equivalent of k D =0.25 in each marker genotype group (Song et al 1999). Table 1 also shows the general expressions for CI (1-α) as a function of Z α/2 , δ D , t D , k D and N, and specific values for CI (0.95) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different ploidy levels in Miscanthus, self incompatibility, and the prospect of highly repetitive sequences, as commonly observed in other grasses, will pose challenges for the mapping process of Miscanthus. However, a preliminary M. sinensis map has already been created based on restriction fragment length polymorphisms (Atienza et al 2002), following a crossing design suggested for outcrossing species (Song et al 1999). Whereas single nucleotide polymorphism (SNP) and simple sequence repeat (SSR) de novo discovery will take some effort, markers from close relatives of Miscanthus like sorghum, sugarcane and corn could be readily exploited for the identification of trait-marker associations.…”
Section: Pest and Disease Resistancementioning
confidence: 99%